Exciton Coupling in Redox‐Active Salen based Self‐Assembled Metallacycles. Issue 65 (22nd October 2021) - Herasymchuk, Khrystyna; Allain, Magali; MacNeil, Gregory A.; Carré, Vincent; Aubriet, Frédéric; Leznoff, Daniel B.; Sallé, Marc; Goeb, Sébastien; Storr, Tim
Abstract: The incorporation of a redox‐active nickel salen complex into supramolecular structures was explored via coordination‐driven self‐assembly with homobimetallic ruthenium complexes (bridged by oxalato or 5, 8‐dihydroxy‐1, 4‐naphthoquinato ligands). The self‐assembly resulted in the formation of a discrete rectangle using the oxalato complex and either a rectangle or a catenane employing the larger naphthoquinonato complex. The formation of the interlocked self‐assembly was determined to be solvent and concentration dependent. The electronic structure and stability of the oxidized metallacycles was probed using electrochemical experiments, UV‐Vis‐NIR absorption, EPR spectroscopy and DFT calculations, confirming ligand radical formation. Exciton coupling of the intense near‐infrared (NIR) ligand radical intervalence charge transfer (IVCT) bands provided further confirmation of the geometric and electronic structures in solution. Abstract : Self‐assembly of redox‐active Ni salen donors and Ru dimer acceptors affords a [2+2] rectangle for the shorter acceptor and a catenane for the longer acceptor. Catenane formation is dependent on solvent choice and concentration. Oxidation to form salen ligand radicals results in exciton coupling of the intense near‐infrared intervalence charge transfer band confirming that the macrocycles remain intact upon oxidation.